2014
DOI: 10.1111/jdv.12789
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of paediatric scalp psoriasis with calcipotriene/betamethasone dipropionate scalp formulation: effectiveness, safety and influence on children's quality of life in daily practice

Abstract: In a daily clinical practice cohort of children with scalp psoriasis, calcipotriene/betamethasone dipropionate scalp formulation was effective with a 32.1% improvement of PSSI at week 12 and a maintenance of this effect until 48 weeks of follow-up, in combination with improvement of QoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…In order to avoid separate applications and to enhance patient compliance, a commercially available compounded formulation containing calcipotriol and betamethasone dipropionate has been developed. Three studies describe the efficacy and safety of this formulation in pediatric psoriasis [ 69 71 ]. In a prospective study with a clinical practice cohort, 73 children (aged 3–18 years) with plaque type psoriasis were treated with calcipotriol/betamethasone dipropionate ointment once daily for 4 weeks and 4 days a week thereafter, with a median treatment duration of 35 weeks.…”
Section: Topical Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to avoid separate applications and to enhance patient compliance, a commercially available compounded formulation containing calcipotriol and betamethasone dipropionate has been developed. Three studies describe the efficacy and safety of this formulation in pediatric psoriasis [ 69 71 ]. In a prospective study with a clinical practice cohort, 73 children (aged 3–18 years) with plaque type psoriasis were treated with calcipotriol/betamethasone dipropionate ointment once daily for 4 weeks and 4 days a week thereafter, with a median treatment duration of 35 weeks.…”
Section: Topical Treatmentsmentioning
confidence: 99%
“…Oostveen et al demonstrated the effectiveness of calcipotriene/betamethasone dipropionate gel in pediatric scalp psoriasis (patient ages 4–17 years) within the first 12 weeks of treatment (84 treatment episodes), with maintenance of this effect through the 48 weeks of follow-up. Striae of the skin (arms, trunk and legs) were described in three patients [ 71 ].…”
Section: Topical Treatmentsmentioning
confidence: 99%
“…While being one of the few, if not the only, tools made for pediatric psoriasis, it has not been widely adapted especially since it only looks at a specific subset of psoriasis. For example, Oostveen et al [42] used it in their prospective observational study. While they did not include an adolescent subanalysis, overall patients with scalp psoriasis (mean age 10.8 ± 3.7 years) showed a significant improvement in all 3 constructs when scalp psoriasis was treated with calcipotriene/betamethasone dipropionate [42] .…”
Section: Psoriasis-specific Hrql Measurement Tool: Children's Scalpdementioning
confidence: 99%
“…For example, Oostveen et al [42] used it in their prospective observational study. While they did not include an adolescent subanalysis, overall patients with scalp psoriasis (mean age 10.8 ± 3.7 years) showed a significant improvement in all 3 constructs when scalp psoriasis was treated with calcipotriene/betamethasone dipropionate [42] . Further studies are needed for a deeper comprehension of its strengths and limitations overall and in an adolescent population, but it may have potential use and could be used as a model for further psoriasis-specific HRQL measurement tools.…”
Section: Psoriasis-specific Hrql Measurement Tool: Children's Scalpdementioning
confidence: 99%
“…Three studies used the compounded formulation of calcipotriol and betamethasone dipropionate. 26 28 In a prospective cohort study, 73 children (aged 3–18 years) with plaque-type psoriasis were treated with calcipotriol/betamethasone dipropionate ointment once daily for 4 weeks and 4 days a week thereafter, with a median treatment duration of 35 weeks. An improvement of the PASI score was noticeable after 1 week and progressed at weeks 12 and 24, with maintenance of improvement thereafter to week 35.…”
Section: Managementmentioning
confidence: 99%